Analisis Rasio Keuangan untuk Bisnis yang Berkelanjutan pada Usaha Mikro Kecil dan Menengah - Jaya, Fitra (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The aim of this research is to identify the risks encountered by entrepreneurs in running their business. To find the right solutions in taking action when facing business risks. Research methods are qualitative approaches and survey approaches. Business risk involves external and internal factors that can affect business performance and therefore, an effective risk management strategy becomes a must. In an effort to minimize risk, it is necessary to adopt a proactive approach involving rigorous market monitoring, comprehensive risk analysis, and the implementation of appropriate mitigation strategies. Business success is determined not only by potential profits, but also by the company's ability to identify, evaluate, and manage such risks. Businesses that are able to respond to risks quickly to changing environments and integrate risk management principles holistically will have stronger competitiveness. The need to sexually highlight a continuous awareness of risk, the implementation of appropriate strategies, and a good risk management culture in a business can the sustainability and long-term success of a business.